2019
DOI: 10.1038/s41419-019-1959-5
|View full text |Cite|
|
Sign up to set email alerts
|

TLR4 signaling drives mesenchymal stromal cells commitment to promote tumor microenvironment transformation in multiple myeloma

Abstract: Inflammation represents a key feature and hallmark of tumor microenvironment playing a major role in the interaction with mesenchymal stromal cells (MSC) in cancer progression. The aim of the present study was to investigate the crosstalk between MSCs and myeloma cells (MM) in the pro-inflammatory microenvironment promoting immune evasion and tumor growth. MSC were collected from patients with diagnosis of MGUS (n = 10), smoldering myeloma (n = 7), multiple myeloma at diagnosis (n = 16), relapse (n = 5) or ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
3
37
0
Order By: Relevance
“…In human and mouse models, MM-derived exosomes can hamper myeloid maturation, conferring immature myeloid cells potent immune suppressive activity, through activation of STAT3, leading to increased immunosuppression which favors MM progression 65,66 . Our previous work showed that immune-modulatory factors released by MM-mesenchymal stem cells are able to induce G-MDSC in vitro from healthy peripheral blood mononuclear cells, supporting an evolving concept regarding the contribution of MM microenvironment to tumor www.nature.com/scientificreports www.nature.com/scientificreports/ development and progression through immune-editing 52,67 . While in solid tumors HDN could reflect the composition of immune infiltrate in tumor microenvironment without exerting immune-suppressive activity, HDN in MGUS and MM patients are immune-suppressive and share immune-suppressive features with G-MDSC, associated to increased CD64 and Arg-1, reduced phagocytosis and CD16 25,34,60 .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In human and mouse models, MM-derived exosomes can hamper myeloid maturation, conferring immature myeloid cells potent immune suppressive activity, through activation of STAT3, leading to increased immunosuppression which favors MM progression 65,66 . Our previous work showed that immune-modulatory factors released by MM-mesenchymal stem cells are able to induce G-MDSC in vitro from healthy peripheral blood mononuclear cells, supporting an evolving concept regarding the contribution of MM microenvironment to tumor www.nature.com/scientificreports www.nature.com/scientificreports/ development and progression through immune-editing 52,67 . While in solid tumors HDN could reflect the composition of immune infiltrate in tumor microenvironment without exerting immune-suppressive activity, HDN in MGUS and MM patients are immune-suppressive and share immune-suppressive features with G-MDSC, associated to increased CD64 and Arg-1, reduced phagocytosis and CD16 25,34,60 .…”
Section: Discussionmentioning
confidence: 63%
“…We found ARG1 gene upregulation among the up-regulated genes in MM-HDNs compared to healthy HDNs. Since our previous work showed that ARG1, a transcriptional target of STAT-3 47,48 , STAT-5 49 and STAT-6 50,51 , is increased in granulocytic-like myeloid derived suppressor cells in MM 28,38,52 , associated to inferior outcome after bortezomib treatment 28 , we explored its expression in both MGUS-and MM-HDNs.…”
Section: Arg-1 Target Of Stat-3 Stat-5 and Stat-6 Is Increased In mentioning
confidence: 99%
“…It has been shown that the crosstalk between MM-cells and MSCs mediated by toll-like receptor 4 (TRL4) signaling transforms MSCs into a "malignant" phenotype, which promotes tumor growth and immune escape [27]. The MM-conditioned MSCs have been shown to suppress T-cell activation and proliferation, impair DC maturation and induce Tregs via the secretion of several factors, including IL-6, TGF-β, IL-10, PGE2, and upregulated expression of several surface molecules such as VCAM-1, intracellular adhesion molecule-1 (ICAM-1) and CD40 [27][28][29][30][31][32]. Additionally, MSCs can exert their immunomodulatory activities by the secretion of extracellular vesicles [33,34].…”
Section: Immunosuppression and Immune Exhaustion In Bone Marrow Micromentioning
confidence: 99%
“…Previous studies reported the requirement of a number of procedures, such as the roasting of coffee beans, to obtain their medicinal effects 24 . To clarify whether the roasting procedure is required for the anti-inflammatory effects of coffee extract, we roasted green coffee beans at 220 degrees for different periods (5,10,15, and 20 min) and prepared their extracts (Fig. 7A).…”
Section: Coffee Extract Induced the Expression Of Nrf2 Which Negativmentioning
confidence: 99%
“…In the process of inflammation, macrophage play a central role in through its ability to produce pro-inflammatory mediators, such as nitric oxide (NO), cytokines, and chemokines 1,2 . A number of accumulated researches have evidenced that chronic inflammation is commonly involved in onsets of age-associated diseases, such as cardiovascular disease, diabetes, and cancer [3][4][5] . Therefore, the regulation of inflammatory responses is crucial for preventing malignancy of these inflammation-related diseases.…”
mentioning
confidence: 99%